2016
DOI: 10.1373/clinchem.2015.249136
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CRTC3: A Newly Identified Protein Released by Adipose Tissue That Is Associated with Childhood Obesity

Abstract: BACKGROUND: CREB-regulated transcription coactivator 3 (CRTC3) is found in adipocytes, where it may promote obesity through disruption of catecholamine signaling. We wished to assess whether CRTC3 is a soluble protein secreted by adipose tissue, explore whether CRTC3 is detectable and quantifiable in the circulation, and ascertain whether CRTC3 serum concentrations are related to metabolic markers in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…From the whole transcriptome analysis, we found 1 upregulated gene and 8 downregulated genes in Wilson's disease-HLCs, and these findings might provide invaluable information in future research for developing new therapeutics of Wilson's disease. For example, several studies showed that the CRTC3, a commonly upregulated gene in Wilson's disease HLCs of this study, is linked with obesity [43] and hepatic steatosis [44]. Because the fat accumulation is frequently observed in the liver of Wilson's disease patients, targeting CRTC3 possibly provides a new concurrent treatment with existing medications (e.g., copper chelators) for Wilson's disease patients.…”
Section: Discussionmentioning
confidence: 80%
“…From the whole transcriptome analysis, we found 1 upregulated gene and 8 downregulated genes in Wilson's disease-HLCs, and these findings might provide invaluable information in future research for developing new therapeutics of Wilson's disease. For example, several studies showed that the CRTC3, a commonly upregulated gene in Wilson's disease HLCs of this study, is linked with obesity [43] and hepatic steatosis [44]. Because the fat accumulation is frequently observed in the liver of Wilson's disease patients, targeting CRTC3 possibly provides a new concurrent treatment with existing medications (e.g., copper chelators) for Wilson's disease patients.…”
Section: Discussionmentioning
confidence: 80%
“…Polymorphisms of CRTC1 and CRTC3 are associated with total cholesterol level in plasma, as well as high BMI, obesity and hypertriglyceridemia in Mexican-Americans, Chinese populations and psychiatric patients [14,36,37]. In addition, CRTC3 is found in circulation, partly as a result of adipose tissue secretion in childhood obesity [38], suggesting CRTC3 might have effects in other tissues beyond adipose and act as a “physiological messenger” during obesity. Most recently, polymorphisms in the CRTC1 loci show a significance genome-wide association with body fat percentage.…”
Section: Crtcs and Metabolic Disordersmentioning
confidence: 99%
“…Indeed, CRTC3 is associated with increased obesity risk in Mexican–Americans (Song et al, ). In addition, the serum concentration of CRTC3 has been identified as a new metabolic marker that is related to childhood obesity (Prats‐Puig et al, ). Thus, CRTC3 might be a promising target for the treatment of obesity and related disorders.…”
Section: Role Of Crtc3 In Adipocytementioning
confidence: 99%